Novel multitarget analgesic candidate SZV-1287 demonstrates potential disease-modifying effects in the monoiodoacetate-induced osteoarthritis mouse model - Horváth, Ádám István; Bölcskei, Kata; Szentes, Nikolett; Borbély, Éva; Tékus, Valéria; Botz, Bálint; Rusznák, Kitti; Futácsi, Anett; Czéh, Boldizsár; Mátyus, Péter; Helyes, Zsuzsanna (Frontiers in Pharmacology, 2024)
Introduction Monoiodoacetate (MIA)-induced osteoarthritis (OA) is the most commonly used rodent model for testing anti-OA drug candidates. Herein, we investigated the effects of our patented multitarget drug candidate SZV-1287 (3-(4,5-diphenyl-1,3-oxazol-2-yl) propanal oxime) that is currently under clinical development for neuropathic pain and characterized the mouse model through complex functional, in vivo imaging, and morphological techniques. Methods Knee OA was induced by intraarticular MIA injection (0.5 and 0.8 mg). Spontaneous pain was assessed based on weight distribution, referred pain by paw mechanonociception (esthesiometry), edema by caliper, neutrophil myeloperoxidase activity by luminescence, matrix metalloproteinase activity, vascular leakage and bone remodeling by fluorescence imaging, bone morphology by micro-CT, histopathological alterations by semiquantitative scoring, and glia activation by immunohistochemistry. Then, SZV-1287 (20 mg/kg/day) or its vehicle was injected intraperitoneally over a 21-day period. Results MIA induced remarkably decreased thresholds of weight bearing and paw withdrawal, alterations in the tibial and femoral structures (reactive sclerosis, increased trabeculation, and cortical erosions), histopathological damage (disorganized cartilage structure, hypocellularity, decreased matrix staining and tidemark integrity, and increased synovial hyperplasia and osteophyte formation), and changes in the astrocyte and microglia density in the lumbar spinal cord. There were no major differences between the two MIA doses in most outcome measures. SZV-1287 inhibited MIA-induced weight bearing reduction, hyperalgesia, edema, myeloperoxidase activity, histopathological damage, and astrocyte and microglia density. Conclusion SZV-1287 may have disease-modifying potential through analgesic, anti-inflammatory, and chondroprotective effects. The MIA mouse model is valuable for investigating OA-related mechanisms and testing compounds in mice at an optimal dose of 0.5 mg.